Antimicrobial and antifungal activity of 2-(1H-tetrazolo-5-yl)anilines and products of their structural modifications - O. M. Antypenko; I. M. Vasileva; S. I. Kovalenko (Zaporozhye State Medical University, 2016)
Virtually any molecule of antibiotic can be inactivated in the microbial cell by particular resistance mechanism. In this regard, each antibiotic effectiveness starts to decrease, which necessitates the synthesis of new antimicrobial agents. Aim. To examine the previously synthesized substituted 2-(1H-tetrazolo-5-yl)anilines and products of their structural modification for antimicrobial and antifungal activity. Materials and methods. The study of biological activity was conducted by disco-diffusion method on Mueller-Hinton agar on these strains of microorganisms: Gram-positive cocci (Staphylococcus aureus ATCC 25923, Enterococcus aeruginosa, E. faecalis ATCC 29212), Gram-negative bacteria (Pseudomonas aeruginosa PSS27853, Escherichia coli ATCC 25922), facultative anaerobic gram-negative bacteria (Klebsiella pneumonia) and fungi (Candida albicans ATCC 885653). Results. The studies showed, that the antifungal activity was characteristic only for S-substituted of tetrazolo[1,5-c]quinazoline-(6H)-5-ones(thiones). The growth of gram-positive cocci Staphylococcus aureus and Enterococcus faecalis, more effectively detained 5-(N,N-dialkylaminoethylthio)-tetrazolo[1,5-c]quinazolines (4.4-4.6). 1-(2- (1H-tetrazolo-5-yl)-R1-phenyl)-3-R2-phenyl(ethyl)ureas (2.1-2.31) were more selective against Staphylococcus aureus and Enterococcus faecalis. Analysis of «structure-activity relationship» showed, that the introduction of halogen to the aniline fragment leads to increase of activity. Thus, the compound 2.3 with fluorine stopped the growth of Escherichia coli and Klebsiella pneumonia for 31 mm and 21 mm, respectively. Structures with chlorine (2.4) and bromine (2.5) stopped the growth of Pseudomonas aeruginosa at 20 mm and 23 mm, respectively. And the presence of trifluoromethyl group in the phenylureide fragment and chlorine in aniline fragment of compound 2.27 led to the highest growth delay zone 25 mm. Among the investigated compounds only 1-(4-methoxyphenyl)-2-(tetrazolo[1,5-c]quinazoline-5-ylthio)-ethanone (4.13) and 1-ethyl-3-(5-fluoro-2-(1H-tetrazolo-5-yl)phenyl)urea (2.3) adversely affect the growth of Klebsiella pneumonia (diameter growth 11 and 21 mm, respectively). Conclusions. Pharmacological screening of 62 synthesized compounds among 2-(1H-tetrazolo-5-yl)anilines, 1-(2-(1H-tetrazolo-5-yl)-R1-phenyl)-3-R2-phenyl(ethyl)ureas, N- and S-substituted tetrazolo[1,5-c]quinazoline-(6H)-5-ones(thiones) allowed to revealed «leader-compounds» with antimicrobial activity which are superior to commonly used antimicrobial antifungal drugs.